Chlorophyll trends are negative for lakes but positive for estuarine–coastal waters - James E. Cloern; Alan D. Jassby (Proceedings of the National Academy of Sciences, 2025)
Nutrient (nitrogen and phosphorus) pollution is an environmental problem of global concern because overenrichment of water bodies increases phytoplankton biomass and ecosystem metabolism, depletes oxygen in bottom waters, and increases the frequency and intensity of harmful algal blooms. These responses to nutrient pollution have motivated policies to reduce anthropogenic nutrient inputs. However, these policies have not been universally implemented and their success at reducing phytoplankton biomass is confounded by other components of global change that regulate the conversion of nutrients into biomass. These regulating processes themselves are changing in the Anthropocene. Our study is an assessment of changing phytoplankton biomass over the period 2000–2019, using chlorophyll a trends measured in 191 lakes and 159 estuarine-coastal sites. Our results show that phytoplankton biomass has decreased in most lakes, increased in most coastal sites, and the largest trends have been predominantly negative for lakes and positive for coastal sites. These results provide evidence of opposing directions of phytoplankton biomass change between lakes and coastal sites in this recent period of unprecedented global change. Nutrient pollution is a knotty environmental problem, and our study indicates that it might be a particularly challenging problem for ecosystems situated in densely populated landscapes where freshwater and sea water meet. Success at overcoming this challenge will require deeper scientific understanding of changes in processes that regulate the conversion of nutrients into phytoplankton biomass, substantial investments of time and resources to reduce nutrient inputs, and a flexible strategy designed to anticipate and adapt to a changing world.